2020
DOI: 10.3389/fmicb.2020.00501
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Downregulates CD163 Expression to Inhibit PRRSV Infection via TLR4-NF-κB Pathway

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) has been recognized to induce proinflammatory cytokine production and modulate the host interferon (IFN) system. Proinflammatory cytokines and type I IFNs contribute to the prevention of viral infection. Lipopolysaccharide (LPS), a specific agonist to Toll-like receptor 4 (TLR4), provokes signal transduction and activates immune response in vivo and in vitro. Here we identified LPS inhibited PRRSV infection in porcine alveolar macrophages (PAMs) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Overexpression of CD163 contributes to the susceptibility of non-permissive cell lines to PRRSV infection. By binding to the three structural proteins GP2, GP4 and GP5, CD163 mediates entry and attachment of the virus to susceptible host cells [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of CD163 contributes to the susceptibility of non-permissive cell lines to PRRSV infection. By binding to the three structural proteins GP2, GP4 and GP5, CD163 mediates entry and attachment of the virus to susceptible host cells [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The model systems we used for functional investigation of water-soluble cyclo-dextrine complex of (all- E )-lutein 5,6-epoxide refer to mechanisms involved in a broad range of nociceptive and inflammatory processes: TPRA1 activation is an important pathway of several inflammatory mediators and irritants on sensory neurons [ 12 , 13 ], and LPS-evoked Toll-like receptor 4 stimulation on macrophages mimics an important component of the inflammatory cascade [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with TPA and LPS, CD163 expression on the cell membrane decreased, along with a reduction in PRRSV production [93]. Another study showed that treatment with LPS inhibited PRRSV infection in PAMs and MARC-145 cells [110]. Since the TLR4 (toll-like receptor 4)-NF-κB (nuclear factor-kappa B) pathway is activated in LPS-treated cells at the early stage of PRRSV infection, proinflammatory cytokines were strongly induced and subsequently reduced the CD163 expression.…”
Section: In Vitro Evidence For Cd163 As the Receptor For Prrsvmentioning
confidence: 99%